2015
DOI: 10.1039/c5ce00424a
|View full text |Cite
|
Sign up to set email alerts
|

Calcite nucleation on the surface of PNIPAM–PAAc micelles studied by time resolved in situ PXRD

Abstract: Biominerals such as CaCO 3 have been studied extensively in an effort to replicate materials found in nature. But understanding and controlling the formation of CaCO 3 has proved a challenge for example in regards to control over crystallite size. The formation of pure calcite has been studied to some degree and a myriad of materials were made utilizing organic additives to control morphology, polymorphism and crystallite size. In this work, these aspects were combined by applying PNIPAM-b-PAAc micelles as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…[1][2][3][4][5] Calcite, the thermodynamically stable polymorph of calcium carbonate, is often not directly formed from solution, but rather through a series of polymorphs starting with an amorphous precursor known as amorphous calcium carbonate (ACC). [6][7][8][9] The stability of ACC is a key factor in its role as a biomineral precursor and in biogenic ACC stabilizers are often present, most commonly Mg ions. 1 The stabilizing effect of Mg 2+ is frequently attributed to the high dehydration energy of magnesium ions, relative to calcium ions, 10,11 which retards the dehydration of the ACC 8 and hence prevents crystallization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Calcite, the thermodynamically stable polymorph of calcium carbonate, is often not directly formed from solution, but rather through a series of polymorphs starting with an amorphous precursor known as amorphous calcium carbonate (ACC). [6][7][8][9] The stability of ACC is a key factor in its role as a biomineral precursor and in biogenic ACC stabilizers are often present, most commonly Mg ions. 1 The stabilizing effect of Mg 2+ is frequently attributed to the high dehydration energy of magnesium ions, relative to calcium ions, 10,11 which retards the dehydration of the ACC 8 and hence prevents crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…1 The stabilizing effect of Mg 2+ is frequently attributed to the high dehydration energy of magnesium ions, relative to calcium ions, 10,11 which retards the dehydration of the ACC 8 and hence prevents crystallization. The stability of synthetic ACC has been studied extensively both with 8,12,13 and without 6,7,9,[14][15][16][17] the incorporation of Mg 2+ . In magnesium-free ACC the stability has been suggested to depend on the mobility of water molecules [17][18][19] and NMR studies 14,20 have suggested that several types of water exist in ACC: translationally rigid, restricted mobile and liquid-like H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…We employed in situ X-ray diffraction [22][23][24][25]29,30] to follow the crystallization of apatite as in our previous work on other types of apatite formation [22,24,25]. We performed in situ synchrotron diffraction in a home built stopped flow apparatus with high temperature stability [24] by mixing equal volumes of a calcium chloride solution (0.4 M) with a sodium phosphate solution (0.24 M) loaded with varying quantities of sodium pyrophosphate (0-0.02 M).…”
Section: Methodsmentioning
confidence: 99%
“…In spite of the important roles of pyrophosphate as a mineralization inhibitor in vivo, no quantitative studies of its impact on nanocrystal formation kinetics have been performed to the best of our knowledge. Herein, we use in situ synchrotron powder diffraction [22][23][24][25] to quantify the impact of pyrophosphate on apatite formation from amorphous calcium phosphate (ACP).…”
Section: Introductionmentioning
confidence: 99%
“…PNIPAM-b-PAAc ( Figure 1) was used as the polymer additive. The polymer has an lower critical solubility temperature (LCST) of 32 °C and we have previously shown how this polymer can be used to afford calcite nanocrystals 22 . The PAAc block acts like an anchor binding the polymer to the surface of the calcite crystal.…”
Section: Introductionmentioning
confidence: 99%